Aktivitas Antioksidan Ekstrak Daun Surian, Mangium, dan Pegagan serta Kombinasinya dalam Formula Krim (Antioxidant Activities of Mangium, Surian, and Pegagan Leaf Extracts and Its Combination in Cream Formulas) - Rita K Sari; Nyoman J Wistara; Deded S Nawawi; Itje Wintarsih; Dewi R Agungpriyono; L N Sutardi; Mawar Subangkit; Vetnizah Juniantito (Jurnal Ilmu dan Teknologi Kayu Tropis, 2016)
The simplicia properties of toona (TS), mangium (AM), and centella (CA) leaves and antioxidant activities of their ethanolic leave extract and their combinations in cream formulas were examined in the present reserach. The ethanolic extracts were partitioned with n-hexane and ethyl acetate. The antioxidant activity of the fractions and their combinations were tested against DPPH. The best combination was formulated in F1, F2, and F3 cream formulas with 0.1, 0.18, and 0.36% of extract, respectively. The formulas antioxidant activity was then tested. The results showed that the water content, ash content, and acidic insoluble ash content of TS, AM, and CA simplicias were ±10%, 3.8-9.7%, and 0.9-1.2% respectively. The yields of n-hexane (FN), ethyl acetate (FEA), and residues (FR) fractions were 6-9, 2, and 5-6% respectively. The antioxidant activity of FEA, FR, and FN was very strong, strong, and weak to inactive, respectively. The best combination was the mixture of 2/3CA, 1/6AM, and 1/6TS (IC50 9 μg ml-1). The antioxidant activity of all cream formulas were higher than refered commercial cream. The IC50 values of formula 1, 2, and 3 were 1109, 596, and 202 μg ml-1, respectively, while the IC50 of refered commercial cream was 2372 μg ml-1.Keywords: antioxidant, centella, cream, extract, mangium, toona